Psychological and Pedagogical Means of Monitoring the Development of Listening Skills - Musiyenko, Alla; Tykhonova, Tetiana (East European Journal of Psycholinguistics, 2014)
The article deals with the problem of the development of listening skills at the lessons of foreign languages. A range of methods and techniques is proposed. The authors share their experience in the sphere of usage the supplementary methods such as questionnaires, scales of diagnostics and self-diagnostics, psychological tests, etc. “Diagnostic and self-diagnostic scale of listening skills”, its structure and different ways of teaching techniques are given. This scale provides a teacher with the objective data of listening skill development of each student and group as a whole. This method helps to involve each student into the listening task, stimulates an adequate differentiation and assessment of one’s listening skills. In its turn it stimulates the development and implementation of different teaching techniques. It leads to individual and group effectiveness. Such questionnaires as “Are you a good listener?” and “Level of your communicative control” may be a good stimulus for conscious speaking control. These techniques were used for foreign language teaching and proved to be efficient.ReferencesBozhenko, L. A., Musiyenko, A. P., Tikhonova, T. B. (1989). Metodicheskie rekomendatsiipo ispolzovaniyu igr I igrovyh situatsyy pri obuchenii inostrannomu yazyku [Guidelines on the useof games and game situations when learning a foreign language]. Kyiv: Kyiv State University.Bubnova, D. V. (2007). Metodyka navchannia dilovogo spilkuvannia anhliyskoyu movoyustudentiv starshyh kursiv vyshchyh tehnichnyh navchalnyh zakladiv. Ph.D. thesis [Guidelines teachingbusiness communication in English students of higher technical educational institutions]. Kyiv.Gamble, T. K., Gamble, M. (1987). Communication Works. New York: Random House.Obozov, N. N., Shchokin, H.V. (1990). Psiholohiya raboty s liudmi. Soviety rukovoditieliu.[Psychology of working with people. Chief Executives Board]. Kyiv: Vydavnytstvo PolitychnoyiLiteratury Ukrainy.